(3GdgGTejGJs - (3GdcejJ Hf RjO Hf NfS GdCSOj, CHh GdeSJgd,J (B126 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN CHh GdaVd YHO GdSdGe GdebQi GdOGgQi MOKfi CHj bG d s
(3BNQgG (B:s
(3Yf GHf YHGS bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3GdfOe JhHI BNQ GdLRA GdChd ef GdgGTejGJ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B233 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B147s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQg GdYGeI(B((3eLGejY (B124) s
Keywords: (3GdMOjK h GdeUWdMs